Islamic banking and finance in the European Union : a challenge - Fahim Khan, M.; Porzio, Mario (Cheltenham; Northampton, MA : Edward Elgar, 2010)
This timely book examines the authorisation of Shari'ah-compliant intermediaries as either credit institutions or as investment companies in the European Union. The book discusses the common origin of Islamic and Western traditions in commercial and banking transactions, reviewing a period in which the Italian merchants and their organizations drove the rebirth of post-medieval society in trade and law. The editors investigate whether the Islamic banking and financial model complies with the European framework, spelling out the different experiences in single Member States (Germany, France, Italy, and the United Kingdom). Notwithstanding the obstacles to being authorised as domestic credit institutions, they conclude that the access of Islamic intermediaries is suitable and may have positive effects on European integration, as well as increasing the competition among the stand-still operators and evoking the ethical dimension of banking and finance
.Includes bibliographical references and index.
oif 23/05/13
Loans
Keywords: Banks and banking; Islamic banking; Islam and state; Finance